Work, Sickness, Absence, and Identity-Work - Trude Gjernes (Nordic Journal of Working Life Studies, 2013)
This article explores how a group of industrial workers experience long-term sickness absence and how they cope with this situation. The article presents data from in-depth interviews with male industrial workers employed in a Norwegian factory. The findings suggest that the factory workers handle their failing health by engaging in activities other than wage work. They did not accept a social situation characterized by passivity, social isolation, marginalization, or loss of self. The workers reported that they lived active lives, reproducing social identities through different bodily activities. It was also made clear that the sickness absence was not a result of their choice, but a result of a failing body and the employer’s inability to adapt work to their health situation.